The Traditional Musical Instrument of West Sumatera As a-non Formal Education - Fris Okta Falma; Ambiyar; Ishak Aziz (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
This study aims to identify and understand the types of traditional instrument from West Sumatra. The method used in this study uses a library method or approach (library research). Data obtained through observation and literature study. The results showed that the traditional instruments of West Sumatra are Talempong, Saluang, Pupuik Batang Padi, serunai, tambua and tansa. Minangkabau traditional musical instruments have various types and forms that usually used on certain occasions. The uniqueness of Minangkabau musical instruments can be seen from how to play it The people of West Sumatra still maintains traditional music because it is considered to function as a medium for non-formal education and cultural identity for the people of West Sumatra